L’histoire sociale de la religion au XIXe siècle : la sécularisation en question - Julien Vincent (Revue Française de Civilisation Britannique)
The study of Victorian religion has been dominated in recent years by an all-round critique of the “secularization thesis” promoted by social historians in the 1960s and 1970s. Studies of institutional religion, of the religious consequences of modernity, or of the Victorian crisis of faith, have recast the traditional concept of secularization. The linguistic turn, by creating an interest in past and present uses of the language of secularization, has brought gender, empire, and cultural history to the centre of Victorian religious history.